PLANNING FOR THE DEVELOPMENT OF A DRINKING WATER DISTRIBUTION SYSTEM NETWORK IN SUNGAI PINYUH - Muhammad, Vira Fadila; Kadaria, Ulli; Purnaini, Rizki (Fakultas Teknik Universitas Tanjungpura, 2024)
The increasing water demand due to population growth and territorial expansion has significantly outpaced the natural water supply in Sungai Pinyuh, Kalimantan Barat. This sub-district, part of the Mempawah Regency, faces challenges such as insufficient access to clean water, deteriorating pipe infrastructure, and environmental pollution affecting water quality. To address these issues, a study has been undertaken to plan a comprehensive development of the drinking water distribution system in Sungai Pinyuh, guided by the Regional Regulation of Mempawah Regency No. 3 of 2014. The planning utilizes EPANET software, a tool developed by the U.S. Environmental Protection Agency (EPA), which allows for the simulation of dynamic conditions in the water distribution system. EPANET helps create detailed maps of the pipe network, determine pump and reservoir locations, and specify pipe characteristics. The software